Successful career and life planning : the systems thinking approach (Crisp Pub. Menlo ParkUS, 2000)
Teaches how to use strategic planning to design, build and sustain a productive and successful life and career. Argues that strategic career and life planning is based on 3 premises viz. planning is integral to life, people support what they create, and systems thinking with its focus on outcomes. Presents output, feedback, input and throughput as the key elements of systems thinking. Explains how to define future long-term goals and use the systems thinking design to achieve them.
Located in the Learning Resource Centre